PENDIDIKAN KARAKTER DALAM GEGURITAN NITI RAJA SASANA SEBAGAI PENGUATAN MODERASI BERAGAMA - Gunada, I Wayan Agus; Harnika, Ni Nyoman; Lestari, Ni Wayan Ria; Rahmanu, I Wayan Eka Dian (Jurnal Lektur Keagamaan, 2024)
This study explores the intrinsic values of character education and religious moderation as depicted in the Niti Raja Sasana geguritan, a literary work rich in noble values. The geguritan primarily focuses on leadership concepts, specifically the philosophical notions of “bratanembelas” and “catur pariksa”. These concepts and their inherent values are pertinent to character education and the reinforcement of religious moderation. Given the significant threat posed by radicalism and intolerance to the unity of Indonesia, it is crucial to fortify and internalize character values and religious moderation from an early age. This research employs a descriptive qualitative approach, with data collected through interviews and literature reviews. The study found that the leadership concepts in the Niti Raja Sasana geguritan serve as guidelines for leaders, embodying ethical and moral values that align with character education. Furthermore, tolerance, a key aspect of these leadership concepts, is essential for navigating societal dynamics and differences, reflecting the core of religious moderation. Additionally, the geguritan is much embedded with values of character and religious moderation. This study is expected to serve as a reference for the enhancement of character education and religious moderation, contributing to efforts to curb the proliferation of radical and intolerant ideologies.